Dynamic interference in the resonance-enhanced multiphoton ionization of hydrogen atoms by short and intense laser pulses - Müller, Anne-Dorothea; Cederbaum, Lorenz S. (Chemical physics, 2018)
Photoionization of the hydrogen atom by intense and short coherent laser pulses is investigated from first principles by a numerical solution of the time-dependent Schrödinger equation in the dipole-velocity gauge. The considered photon energies are resonant to the 1s→2p excitation, and the pulse intensities are high enough to induce Rabi floppings. The computed resonance-enhanced two-photon ionization spectra as well as the three-photon above threshold ionization spectra exhibit pronounced multiple-peak patterns due to dynamic interference. Fingerprints of dynamic interference can also be seen directly in the radial density of the photoelectron. The impact of the variation of the pulse intensity and photon energy on the dynamic interference is investigated, and the angular distribution of the emitted electrons is analyzed in some details. The present precise numerical results confirm our previous theoretical predictions on the two-photon ionization spectra (Demekhin and Cederbaum, 2012) made within a minimal few-level model.
Gesehen am 03.05.2019
Available online: 21 October 2017